PENGARUH ATRIBUT PRODUK PERAWATAN MUSTIKA RATU TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI WILAYAH JAKARTASELATAN - Siska Wulandari, (2013)
This study aims to identify and prove the significant influence of product attributes (brand, packaging, design, and price) on consumer purchasing decisions mustika ratu care. By using simple linear regression analysis method. Samples taken from the consumer do teenagers or adults who use care Mustika Ratu in South Jakarta because the object has been studied using the treatment because of age and also so it is worth to study. By using SPSS 17. The sample used in this study were 130 respondents, 30 Research Trial and 100 research. The results showed that the product attributes have a strong and positive impact on purchasing decisions care products. The results achieved in this study are expected to be taken into consideration for the advancement of the company and beneficial to the authors as well as those who reading this paper.